KEEFEKTIFAN LEMBAGA PASAR LELANG CABAI MERAH DI KECAMATAN PANJATAN KABUPATEN KULON PROGO - Patrianisya Devi; Harsoyo Harsoyo; Subejo Subejo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
Research was done in Panjatan District Kulon Progo Regency aimed to know the effectiveness of auction market institution for red chili in Panjatan District and also to know the factors which influence to the effectiveness of auction market institution for red chili. This research used descriptive analytic method. District, subdistrict, and farmer groups were taken by Purposive method. Sample members were taken from every farmer group sample by using Simple Random Sampling with total amount of 60 farmers. Data were analized by Proportion Test and Multiple Regression Analysis. The results of research showed that the most of farmer in Panjatan District Kulon Progo Regency have perception that the auction market institution for red chili has a high effectiveness. Farmer’s attitude and farmer group leader role give positive influence to the effectiveness of auction market institution for red chili, education level of farmers give negative influence to the effectiveness of auction market institution for red chili, whereas age, motivation, and the selling price of chili do not influence to the effectiveness of auction market institution.